2012
DOI: 10.14227/dt190412p51
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Equivalence Studies of Generic Metformin Hydrochloride Tablets and Propranolol Hydrochloride Tablets Under Biowaiver Conditions in Lagos State, Nigeria

Abstract: This study used biowaiver conditions to assess bioequivalence of some generic products used in Nigeria. None of the generic samples tested met biowaiver conditions; therefore, in vivo bioequivalence studies are required to ascertain therapeutic equivalence. To take advantage of the cost savings of using in vitro dissolution as a surrogate for bioequivalence studies, manufacturers of generic products need to consider factors that affect solubility and permeability of their products when formulating them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
1
10
0
3
Order By: Relevance
“…Nevertheless, Wong and Ngo [32] reported that even if multiple generic MH IR tablets had different dissolution profiles in vitro, the in vivo performance might not likely be diverted to a clinically significant extent. The previous conclusion was in complete accordance with Oyetunde et al [29] who discussed in their study that even if the dissolution performance of BSC class III drug products were found to be relatively slow, they may still have similar in vivo absorption.…”
Section: Beaker Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, Wong and Ngo [32] reported that even if multiple generic MH IR tablets had different dissolution profiles in vitro, the in vivo performance might not likely be diverted to a clinically significant extent. The previous conclusion was in complete accordance with Oyetunde et al [29] who discussed in their study that even if the dissolution performance of BSC class III drug products were found to be relatively slow, they may still have similar in vivo absorption.…”
Section: Beaker Methodssupporting
confidence: 87%
“…This may be due to differences in rate and extent of absorption [26], excipients and manufacturing processes [27] or the manufacturing variables such as the mixing effect and granulation procedure [7]. Few studies compared the performance of innovator and generic products of MH in different countries [26,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…14 An in vitro dissolution study on four generic products of metformin showed that none of the four brands of metformin tested met this requirement because the innovator product and two others did not achieve 85% dissolution in 15 min. 16 In a similar study conducted by Olusola et al 17 in 2012 on eight generic products of metformin, only three met the criteria for BCS biowaiver after a physiochemical equivalence testing. Thus, using an in vitro dissolution profile as a surrogate for in vivo BE is still debatable as in vivo-in vitro correlation has not been established for metformin in most cases.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, using an in vitro dissolution profile as a surrogate for in vivo BE is still debatable as in vivo-in vitro correlation has not been established for metformin in most cases. 16 Developing countries will benefit from generic products, unfortunately the resources for testing drug quality is limited. Thus, this study aimed to assess the bioavailability of generic formulations of metformin versus that of the innovator product.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution profiles having value of f 2 equal to or greater than 50 were considered as similar and ones having value below 50 were considered statistically different from the reference. The f 2 values were calculated using the formula below as per US FDA guidelines 11,29,30 ,…”
Section: In-vitro Dissolution Testingmentioning
confidence: 99%